The Extent of the Arbitrator's Immunity from Civil Liability Compared to the Judge's Immunity (Comparative Study) - ALQUDAH, Yassin Ahmad; ALKHSEILAT, Abdullah Ahmed (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020DO - 10.14505/jarle.v11.3(49).02, 2020)
This study aims at the legal dimensions of the legislative deficiency of the arbitrator's immunity from civil liability in the Jordanian Arbitration Law, which the legislator granted to the judge. The researchers reached the need to amend the provisions of the Jordanian Arbitration Law to grant immunity to the arbitrator, especially since the work is similar to that of a judge. The judicial immunity of the arbitrator is civil liability in comparison with the immunity of the judge Jordanian and Egyptian lawmakers have imposed restrictions on the civil (commercial) arbitrator's responsibility for the mistakes he makes while performing his arbitral mission, This is to encourage arbitration, compared to the position of the arbitrator over the judge's function, hence granting the Jordanian legislator and the Egyptian legislator and the judgments of the commercial arbitrator judicial immunity similar to that enjoyed by the judge but much less than the immunity of the judge. We therefore consider it appropriate to examine the arbitrator's immunity, beginning with a shedding light on the judges' immunity from civil responsibility, given the similarity in the task entrusted to both the judge and the arbitrator, which is to resolve disputes by a legally binding and enforceable judgment. This requires us to present the principle of judicial immunity from civil liability, and the reasons that support and oppose such immunity, in order to determine the judicial immunity of arbitrators of civil liability.